The Face of Christian Hope in the Renewed Funeral Rites - Trojnar, Wiktor (Teologia w Polsce, 2020)
The Second Vatican Council brought a new look at the ultimate reality of man. It has definitely contributed to the deepening of the understanding of the Christian faith and allowed to adapt its message to the needs of modern times. It was from its inspiration that, a few years after the promulgation of the Constitution Sacrosanctum concilium, the Ordo Exsequiarum was reformed, which made it possible to introduce the changes postulated by the Council’s fathers into the funeral liturgy. In accordance with their provisions, the funeral rites were to express more clearly the paschal character of the Christian’s death. Thus, the liturgy of the funeral became a special place for proclaiming Christian hope. It therefore seems necessary, on the basis of the texts of the renewed funeral rites, to notice its paschal character.